Circular RNA biogenesis is decreased in postmortem cortical gray matter in schizophrenia and may alter the bioavailability of associated miRNA - Mahmoudi, Ebrahim; Fitzsimmons, Chantel; Geaghan, Michael P.; Shannon Weickert, Cynthia; Atkins, Joshua R.; Wang, Xi; Cairns, Murray J. (Neuropsychopharmacology (New York, N.Y.), 2019)
Circular RNAs (circRNAs) are a covalently closed subclass of non-coding RNA molecules formed by back splicing of linear precursor RNA. These molecules are relatively stable and particularly abundant in the mammalian brain and therefore may participate in neural development and function. With the emergence of circRNAs activity in gene regulation, these molecules have been implicated in several biological processes, including synaptic plasticity, and we therefore suspect they may have a role in neurobehavioral disorders. Here, we profile cortical circRNAs expression in 35 postmortem cortical gray matter (BA46) schizophrenia and a non-psychiatric comparison group, using circRNA enrichment sequencing. While more than 90,000 circRNAs species were identified in the dorsolateral prefrontal cortex (DLPFC), we observed lower complexity and substantial depletion in subjects with the disorder. Although circRNAs expression was independent of their host gene transcription, alternative splicing rates were lower in samples from cases compared to controls. Gene set analysis of differentially expressed circRNAs host genes revealed significant enrichment of neural functions and neurological disorders. Many of these depleted circRNAs are also predicted to sequester miRNAs that were shown previously to be increased in the disorder, potentially exacerbating the functional impact of their dysregulation through posttranscriptional gene silencing. While this is the first reported exploration of circRNAs in schizophrenia, there is significant potential for dysregulation more broadly in other major mental illnesses and behavioral disorders. Given their capacity for modulating miRNA function, circRNA may play a significant role in the pathophysiology of disease and even be targeted for therapeutic manipulation.